Effects of RANKL inhibition on promoting healing of bone erosion in rheumatoid arthritis using HR-pQCT: a 2-year, randomised, double-blind, placebo-controlled trial. Issue 8 (2nd April 2021) - So, Ho; Cheng, Isaac T; Lau, Sze-Lok; Chow, Evelyn; Lam, Tommy; Hung, Vivian W; Li, Edmund K; Griffith, James F; Lee, Vivian W; Shi, Lin; Huang, Junbin; Kwok, Kitty Yan; et al.
Abstract : Objective: To evaluate the effects of denosumab on erosion healing at 2–4 metacarpophalangeal (MCP) head as determined by high-resolution peripheral quantitative CT (HR-pQCT) in patients with rheumatoid arthritis (RA) with stable disease. Methods: This was a randomised, placebo-controlled, double-blind study. Patients with RA with disease activity score 28 joints (DAS28) ≤5.1 were randomised (1:1) to subcutaneous denosumab 60 mg or placebo once every 6 months for 24 months. The primary outcome was erosion healing at MCP 2–4 on HR-pQCT at 12 months. The effects of denosumab on erosion and joint space parameters on HR-pQCT and radiographs, disease activity and health assessment questionnaire-disability index (HAQ-DI) were also examined. Results: At 24 months, HR-pQCT images were analysed in 98 patients. One-third of the patients achieved sustained low disease activity throughout the study. At 12 months, changes in erosion parameters on HR-pQCT were similar between the two groups. At 24 months, new erosions (19% vs 9%, p=0.009) and erosion progression (18% vs 8%, p=0.019) were more common in the placebo group than the denosumab group. Erosion healing was seen in a significantly higher proportion of patients in the denosumab group (20% vs 6%, p=0.045) at 24 months. No significant changes in joint space parameters on HR-pQCT, van der Heijde-Sharp erosion score, DAS28 and HAQ-DI were observed in the two groups at 12 and 24 months. Conclusion: Although no differences in erosion parameters were observed at 12 months, denosumab was more efficacious than placebo in erosion repair on HR-pQCT after 24 months. Trial registration number: NCT03239080 .